CHARACTERISTICS OF WORK RELATED MUSCULOSKELETAL DISORDERS IN COMANDOS (Vietnam Journal of Community Medicine, 2021)
Objective: To describe the characteristics of work related musculoskeletal disorders in commandos. Subjects and methods: A cross-sectional descriptive study on 1,500 servicemen of the comando forces participating in the investigation of musculoskeletal disorders. Results: The prevalence of chronic musculoskeletal pain (in 12 months) was 60% of which the pain was mainly found in the nape, shoulder and lower back. Chronic musculoskeletal pain having to leave work only had a low rate (17,73%), most in the lower back with 9.40%. The nape and lower back had the highest rate of acute musculoskeletal pain, 21.40% and 21.27%, respectively. The Comandos soldiers worked mainly in standing and sitting positions. High REBA scores associated with musculoskeletal pain in the neck, elbows, wrists or hands, upper and lower back, thighs, and knees. Conclusion: The rate of musculoskeletal disorders in the commandos was 60%, of which the nape, shoulder, and lower back are the areas with the highest rate of musculoskeletal pain. Standing and sitting are the two main working positions of commandos. High REBA scores are associated with musculoskeletal pain in commandos.
Keywords: Work related musculoskeletal disorders, commandos